The fabulous Baker boys [videorecording (DVD)] - Bridges, Jeff, 1949-; Pfeiffer, Michelle, 1957-; Bridges, Beau (LIVE Entertainment, 1998)
The Baker brothers have played every hotel and cocktail lounge they could book in the last 15 years. They book Susie Diamond, a hard-talking beauty with a terrific voice, and the trio become an instant success.